‘Freemartin’ Like Congenital Anomaly in a Goat Kid (Capra hircus) - Satheshkumar, Soundarapandian; Prakash, Subramanian; Prabaharan, Vaiyapuri (The Indian Journal of Animal Reproduction, 2025)
Clinical investigation of a goat kid brought with the history of straining and genital abnormality revealed the presence of an enlarged clitoris and blind-ended vaginal canal. A non-patent uterine horn-like structure and absence of ovaries was confirmed by ultrasonographic investigation. The case was confirmed to be a rare incidence of ‘freemartin’ like congen ital anomaly in a goat kid.